Proceedings of the International Scientific Conference - Sinteza 2017 2017
DOI: 10.15308/sinteza-2017-214-219
|View full text |Cite
|
Sign up to set email alerts
|

IT Support for Descriptive Geometry Course for Engineering Students

Abstract: Constant development of IT technologies and Descriptive Geometry (DG) course time limitation pose new challenges in engineering education methodology. A wide range of supportive digital tools for knowledge transfer exist for reaching certain goals related to young engineers' spatial perception, imagination and comprehension. The combination of classic DG teaching methods and 3D software environment as a demonstration tool was tested on three generations of students. Statistical analyses based on data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This has significant implications, even for training children to behave safely in traffic. Additionally, numerous studies have shown that solving educational tasks on a computer can help develop children's skills (23,(29)(30)(31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has significant implications, even for training children to behave safely in traffic. Additionally, numerous studies have shown that solving educational tasks on a computer can help develop children's skills (23,(29)(30)(31).…”
mentioning
confidence: 99%
“…However, one study that compares a paper-based approach with a technology-based one in relation to collection of space data is that by Yabiku et al ( 21 ) They found that using a tablet computer is quite feasible and yields higher accuracy than paper methods. Moreover, some studies have shown that children perform better when they take tests on tablets rather than on paper ( 14 , 22 , 23 ). Research conducted in 2018 in which the behavior of children in “traffic” in the playground and in a simulated situation on the computer was examined, also supports this.…”
mentioning
confidence: 99%